A Common Mechanism for Perceptual Reversals in Motion-Induced Blindness, the Troxler Effect, and Perceptual Filling-In. (January 2017) - Devyatko, Dina; Appelbaum, L. Gregory; Mitroff, Stephen R.
Several striking visual phenomena involve a physically present stimulus that alternates between being perceived and being "invisible." For example, motion-induced blindness, the Troxler effect, and perceptual filling-in all consist of subjective alternations where an item repeatedly changes from being seen to unseen. In the present study, we explored whether these three specific visual phenomena share any commonalities in their alternation rates and patterns to better understand the mechanisms of each. Data from 69 individuals revealed moderate to strong correlations across the three phenomena for the number of perceptual disappearances and the accumulated duration of the disappearances. Importantly, these effects were not correlated with eye movement patterns (saccades) assessed through eye tracking, differences in motion sensitivity as indexed by dot coherence and speed perception thresholds, or simple reaction time abilities. Principal component analyses revealed a single component that explained 67% of the variance for the number of perceptual reversals and 60% for the accumulated duration of the disappearances. The temporal dynamics of illusory disappearances was also compared for each phenomenon, and normalized durations of disappearances were well fit by a gamma distribution with similar shape parameters for each phenomenon, suggesting that they may be driven by a single oscillatory mechanism.